Distribution of Trans-Anethole and Estragole in Fennel (Foeniculum vulgare Mill) of Callus Induced from Different Seedling Parts and Fruits - Abd El-Moneim Mohamed Radwan AFIFY; Hossam Saad EL-BELTAGI; Anwer Abd El-Aziz HAMMAMA; Mahassen Mohamed SIDKY; Omneya Farouk Ahmed MOSTAFA (Notulae Scientia Biologicae, 2011)
In the present study, seeds from local cultivar of fennel were germinated on Murashige and Skoog medium (MS) without plant growth regulators. Different types of explants from the growing seedling such as cotyledonal leaves, hypocotyls, epicotyls and roots were cultured on MS medium, contained different concentrations of 2,4-dichlorophenoxyacetic acid (2,4-D) either alone or with kinetin. Differential responses in the essential oil constituents were observed in the induction and development of callus. The major components of essential oils includes estragole, trans-anethole, limonene and fenchone were studied under different conditions to find out the best methods which could be used to reduce the amount of estragole (not favorite for human consumption) and increase the amount of trans-anethole.